2018
DOI: 10.1038/s41598-018-22897-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive markers of cardiovascular risk in patients with subclinical hypothyroidism: A systematic review and meta-analysis of 27 case control studies

Abstract: It has been reported that subclinical hypothyroidism (SCH) is closely related to subclinical atherosclerosis. According to the impact of SCH on noninvasive markers of cardiovascular risk, we fulfilled a meta-analysis of included studies to provide an integrated overview. We searched electronic databases and included all relevant studies involving SCH and epicardial adipose tissue (EAT), carotid intima-media thickness (CIMT), pulse wave velocity (PWV), flow-mediated dilation (FMD) and glyceryl trinitrate-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…Among the 52 included eligible MAs, 4628–73 (46/52, 88.5%) were published in English, and the rest74–79 (6/52, 11.5%) were published in Chinese. The 52 included MAs contained 685 studies, with an average of 13.2 (range: 3–39) studies per article.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 52 included eligible MAs, 4628–73 (46/52, 88.5%) were published in English, and the rest74–79 (6/52, 11.5%) were published in Chinese. The 52 included MAs contained 685 studies, with an average of 13.2 (range: 3–39) studies per article.…”
Section: Resultsmentioning
confidence: 99%
“…Ten39 40 43 49 57 58 65 68–70 MAs were about the associations between OH and other diseases, and 3528–36 38 42 44–47 50–56 59–64 66 67 75–79 MAs have shown the associations between SCH and other diseases. Seven37 41 48 71–74MAs have investigated the effects of both OH and SCH on other diseases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…confirmed the significant association between SCH and cardiovascular risk with arterial wall thickening and stiffening and endothelial dysfunction. They suggested that these findings could help to establish cardiovascular prevention strategies for SCH patients ( 21 ). Our study results are consistent with that meta-analysis, and also proved the significant negative correlation between CIMT and endothelial function in both overt and subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%